ПРОБЛЕМА ФОРМУВАННЯ ПРОФЕСІЙНОЇ КОМПЕТЕНТНОСТІ МАЙБУТНЬОГО ФАХІВЦЯ В КОНТЕКСТІ ВПРОВАДЖЕННЯ КОМПЕТЕНТНІСНОГО ПІДХОДУ У ВИЩИХ ПРОФЕСІЙНИХ НАВЧАЛЬНИХ ЗАКЛАДАХ УКРАЇНИ (Педагогіка вищої та середньої школи, 2008)
This article considers the problem of formation of the professional competence of future specialists in the context of realization of the Competence-Based Approach in the higher professional school. It reveals the main points of view on its introduction and its results; it studies the structure and the main constituents of the professional competence of future specialists.